Crecimiento, y estado fitosanitario de Simarouba amara "marupa" de la plantación N° 21 del CIEFOR - Puerto Almendra, Loreto - Perú. 2021 - Luque García, Mitzi Johana (2022)
The study was carried out in Forest Parcel No. 21 of 1 ha in Ciefor - Puerto Almendras, evaluating 200 Simarouba amara plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by band 1 and 8 with a value of 0,10 cm between the first and last evaluation. Likewise, in height the greatest increase was presented by band 6 with a value of 5,79 cm. The Chi-square test indicates that there is a significant difference between the averages of increase in diameter - height and the bands (p-value = 0,00 <? = 0,05). The survival of cedar plants varies between 50% to 95% survival, while mortality reached 54,82%. The highest number of plants presented GOOD quality with 129 seedlings that represents 27,64% of the total, followed by REGULAR quality with 9 live individuals that indicates 4,52 % and, finally, the least amount of individuals were observed in BAD quality with 3 seedlings that represented 1,51 % of the total. At a general level in the experiment Good quality (band 1, 2, 3, 4, 6, 7) was recorded for the Simarouba amara seedlings at the end of the study. Similar studies are needed with other native forest species in Ciefor - Puerto Almendras.